Pregnancy Class Program in West Java Province: a literature review - Rahmawaty, Dinta; Laro, Maria Natalia; Rajagukguk, Vivi Rosalin; Wahyuningsih, Windu Syawalina (Universitas Gadjah Mada, 2025)
Purpose: This study aims to analyze the implementation of the Pregnancy Class Program in West Java Province and develop policy recommendations to enhance maternal health outcomes. Method: A literature review was conducted using journal databases including ResearchGate, ScienceDirect, and Google Scholar. Articles published between 2018 and 2024 were retrieved using keywords such as “evaluation,” “implementation,” “policy,” “pregnancy class,” “prenatal education,” and “West Java.” From 58 identified articles, six studies that met the inclusion criteria were selected and thematically analyzed. Results: The review identified several challenges in implementing pregnancy classes in West Java, including low participation rates, limited partner and family involvement, and barriers faced by working mothers. Digital innovations, such as video-based education and online classes, have effectively increased maternal knowledge and participation. Furthermore, family-oriented approaches and prenatal yoga sessions had a positive impact on maternal preparedness and confidence. Conclusion: The pregnancy class program holds significant potential to improve maternal and neonatal outcomes in West Java. However, to maximize the effectiveness of its online educational sessions and offline interactive activities, such as prenatal yoga, is recommended. Additionally, to maximize its effectiveness, high-quality video content, continuous training for healthcare workers, and sufficient funding should be integrated to enhance the program's reach and impact.